Vogt-Koyanagi-Harada disease – a rare entity in the Polish population – a case report - Słomska, Martyna; Kręcicka, Julia; Kaczmarek, Radosław; Turno-Kręcicka, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2020)
Vogt-Koyanagi-Harada (VKH) disease is an idiopathic autoimmune reaction against tissues containing melanocytes. Typical eye symptoms are bilateral granulomatous panuveitis and serous retinal detachment (SRD). At a later stage it leads to extensive depigmentation of the fundus (“sunset glow fundus”). The symptoms are accompanied by neurological, auditory or integumentary disorders. The diagnosis is based on clinical findings. In this article we present a case of a 39-year-old man, who had been mistakenly treated for many months before the correct diagnosis was made. Our research is one of the first publications describing Vogt-Koyanagi-Harada disease in the Polish population; therefore this diagnosis is rarely considered.